Comparison of health-related quality of life in patients with atrial fibrillation treated with catheter ablation or antiarrhythmic drug therapy: a systematic review and meta-analysis protocol. Issue 8 (21st August 2017) - Allan, Katherine S; Henry, Shaunattonie; Aves, Theresa; Banfield, Laura; Victor, J Charles; Dorian, Paul; Healey, Jeff S; Andrade, Jason; Carroll, Sandra; McGillion, Michael
Abstract : Introduction: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia and causes patients considerable burden; symptoms such as palpitations and dyspnoea are common, leading to frequent emergency room visits. Patients with AF report reduced health-related quality of life (HQOL) compared with the general population; thus, treatments focus on the restoration of sinus rhythm to improve symptoms. Catheter ablation (CA) is a primary treatment strategy to treat AF-related burden in select patient populations; however, repeat procedures are often needed, there is a risk of major complications and the procedure is quite costly in comparison to medical therapy. As the outcomes after CA are mixed, an updated review that synthesises the available literature, on outcomes that matter to patients, is needed so that patients and their healthcare providers can make quality treatment decisions. The purpose of this review protocol is to extend previous findings by systematically analysing randomised controlled trials (RCTs) of CA in patients with AF and using meta-analytic techniques to identify the benefits and risks of CA with respect to HQOL and AF-related symptoms. Methods and analysis: We will include all RCTs that compare CA with antiarrhythmic drugs, or radiofrequency CA with cryoballoon CA, in patients with paroxysmal or persistent AF. To locate studies we will perform comprehensive electronic database searches from database inception to 4 April 2017, with no language restrictions. We will conduct a quantitative synthesis of the effect of CA on HQOL as well as AF-related symptoms and the number of CA procedures needed for success, using meta-analytic techniques. Ethics and dissemination: No ethical issues are foreseen and ethical approval is not required given that this is a protocol. The findings of the study will be reported at national and international conferences, and in a peer-reviewed journal using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Trial registration number: In accordance with the guidelines, our systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 6 March 2017 and was last updated on 6 March 2017 (registration number CRD42017057427). Protocol amendments: Any protocol amendments will be documented on the International Prospective Register of Systematic Reviews (PROSPERO) and in the final manuscript and indicated as such.